Application of the Conceptual Model of Buddhist Counseling and Guidance Through Online Media During the Covid 19 - Sulaiman Girivirya (Educational Studies: Conference Series, 2021)
The foundational teaching of the four noble truths is the foundation of the Buddhist counseling psychology conceptual paradigm. The Four Noble Truths are the most fundamental teachings of Buddhism, and both Mahayana and Theravada Buddhists subscribe to them. This model is applied in the form of training by measuring prior concept knowledge and training. After a final exam was done at the implementation of the program's second session, the participants of the application "Buddhist Counseling Psychology Training Model" increased their level of knowledge mastery from 46.67 percent to 78.24 percent. This finding implies that Buddhists need to improve their knowledge of Buddhist Guidance and Counseling resources while seeking direction or resolving personal, family, or communal issues. The participants' strength after this activity was also demonstrated by a variety of enthusiastic inputs.